Development of a universal serial bus hub with protection circuits - Mohd Razuan, Mohamed Said (2008)
Objective of this project is to design, construct and develop a Universal Serial Bus (USB) hub with protection circuits. There are two types of USB hub according to their supplied power that is self powered USB hub and bus powered USB hub. Self powered USB hub means that USB hub get their power from power supply, and bus powered USB hub means that USB hub get their power from personal computer. This project only develops one type of USB hub which is self powered USB hub. In order to wider the scopes of this project, this project is added with powered circuits to make it more firm and hard to be blow out. The most important thing in designing this project is to manage input power and supply power for each port. Four ports are chose to be implementing in the circuits to be connecting into one personal computer. This project also will discuss the result in connecting four computer devices onto one personal computer using final and complete developed gadget.